The smart city concept and its importance in the development of urban space - Zakrzewska-Półtorak, Alicja (Koncepcja inteligentnych miast i jej znaczenie w rozwoju przestrzeni zurbanizowanych, 2015)
The aim of this paper is to discuss the smart city concept and indicate how its implementation may influence the efficient development of urban space. The paper is a review of the results of research on the smart city concept, smart cities in the European Union and selected aspects of modern urban space development. The author used above all a descriptive method and simple statistical methods. As the paper proves, the implementation of the smart city concept can facilitate and support the development of urban space. The main conclusions concern its impact on awareness in society, civic participation, creative attitudes, entrepreneurial activities and innovative solutions
Biblioteka Regionalisty, 2015, Nr 15, s. 103-112
Keywords: city; urban space; development; smart city; miasto; przestrzeń zurbanizowana; rozwój; inteligentne miasto